Intramolecular Thermal Cyclizations of Substituted N-Phenyl Cinnamamides by Polyphosphoric Acid - TIWARI, ALKA (Asian Journal of Chemistry, 2010)
An efficient and simple method has been devised for the synthesis of substituted 3,4-dihydrophenyl carbostyrils using polyphosphoric acid as a reagent in excellent yields (80-95%).